Beyond Obligation: Reasons and Supererogation. (16th September 2015) - Ferry, Michael
Abstract : Morality makes many demands on us. But few of us believe that we must do, morally speaking, the best that we can. There is a category of acts, the supererogatory, that involve going beyond our obligations. It seems perfectly plausible, for example, that the moral perfectionist would donate her fifty dollars to UNICEF though the rest of us are within our moral prerogative when we buy ourselves shoes instead. Although donating to UNICEF is considered especially good, it is usually accepted that morality permits us to buy the shoes; buying shoes is not considered a moral failing. When we consider our reactions to examples like this one, the idea that morality does not demand that we do our best is quite intuitive. On its face, however, it is rather curious. If in a given situation it would be morally better to give to UNICEF than to buy shoes, then how is it not a moral failing when one buys the shoes?